Analysis of Customer Self-Congruity Factors Influence on Customer Loyalty of SME Coffee Shop in Indonesia - David Ricardo Santoso; Edwin; Setiadi, A. S. (JURNAL ECONOMINA, 2026)
This study will take the scope of the food and beverage industry sector in SME scale. This study will approach coffee shop sub-sector in management and psychological perspective. This study focuses on how self-congruity becomes a factor that moderates the relationship between service quality and brand image on customer satisfaction and customer satisfaction effect on customer loyalty in coffee shop businesses in Indonesia. The approach will be taken with a quantitative approach and structural equation modeling. This study found that in coffee shop customers self-congruity strengthens a positive impact on service quality and brand image. Self-Congruity plays an important role in dealing with customer perceptions of their brand loyalty.